2017
DOI: 10.1002/pmic.201700256
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic and Proteomic Analyses Reveal a FluG‐Mediated Signaling Pathway Relating to Asexual Sporulation of Antrodia camphorata

Abstract: Medicinal mushroom Antrodia camphorata sporulate large numbers of arthroconidia in submerged fermentation, which is rarely reported in basidiomycetous fungi. Nevertheless, the molecular mechanisms underlying this asexual sporulation (conidiation) remain unclear. Here, we used comparative transcriptomic and proteomic approaches to elucidate possible signaling pathway relating to the asexual sporulation of A. camphorata. First, 104 differentially expressed proteins and 2586 differential cDNA sequences during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 31 publications
(30 reference statements)
2
18
0
Order By: Relevance
“…In this study, ~66% of the predicted fungal genes could be detected during the algicidal process via RNA-Seq. The number of detected genes far exceeded that obtained via proteomic techniques, which was also observed in many other studies (Bai et al, 2015 ; Li et al, 2017 ). A previous proteomic study showed that pyruvate metabolism and tricarboxylic acid cycle pathways, carbon metabolism, selenocompound metabolism, sulfur assimilation and metabolism, and several amino acid biosynthesis pathways had been enriched (Gao et al, 2017 ).…”
Section: Discussionsupporting
confidence: 52%
“…In this study, ~66% of the predicted fungal genes could be detected during the algicidal process via RNA-Seq. The number of detected genes far exceeded that obtained via proteomic techniques, which was also observed in many other studies (Bai et al, 2015 ; Li et al, 2017 ). A previous proteomic study showed that pyruvate metabolism and tricarboxylic acid cycle pathways, carbon metabolism, selenocompound metabolism, sulfur assimilation and metabolism, and several amino acid biosynthesis pathways had been enriched (Gao et al, 2017 ).…”
Section: Discussionsupporting
confidence: 52%
“…Differentially expressed genes (DEGs) were identified by DEseq ( q < 0.05 and difference multiple |FoldChange| > 2), , annotated using the Conserved Domain Database (CDD), the EuKaryotic Ortholog Groups (KOG), the Clusters of Orthologous Groups of proteins, and the NCBI nonredundant protein sequences. Additionally, gene ontology (GO) was determined using the UniProt annotation information based on Wisprot and TrEMBL, and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotations were also gathered using the KEGG Automated Annotation Server. , Annotations were followed by clustering analysis. Last, Cluster Profiler was used to analyze the KEGG pathway and KOG classification enrichment of the DEGs and to map the network based on the results of gene function enrichment analysis …”
Section: Methodsmentioning
confidence: 99%
“…Additionally, gene ontology (GO) was determined using the UniProt annotation information based on Wisprot and TrEMBL, and Kyoto Encyclopedia of Genes and Genomes (KEGG) annotations were also gathered using the KEGG Automated Annotation Server. 35,37 Annotations were followed by clustering analysis. Last, Cluster Profiler was used to analyze the KEGG pathway and KOG classification enrichment of the DEGs and to map the network based on the results of gene function enrichment analysis.…”
Section: Effects Of Oxidative Stressmentioning
confidence: 99%
“…Revealing the regulatory mechanism is helpful to rationally adjust and control the asexual sporulation and thereby improve the efficiency of preparation for inoculum during submerged fermentation of A. cinnamomea . In our previous research, the molecular regulatory mechanism mediated by FluG in the asexual sporulation of A. cinnamomea submerged fermentation was revealed [ 15 ]. The present work aims to further study the sporulation of A. cinnamomea under nutrition deficiency in the late stage of submerged fermentation, and explore the molecular regulatory mechanism underlying asexual sporulation induced by nutrient limitation in submerged fermentation of A. cinnamomea .…”
Section: Introductionmentioning
confidence: 99%